Strategi Coping pada Caregiver Penderita Stroke - Fahrunnisa Fahrunnisa; Mutingatu Solichach (UIN Sunan Kalijaga, 2017)
This study aimed to reveal deeply the coping stress used by caregiver in its treatment to a spouse who have experienced stroke. This study used qualitative method with case study approach, using interview as data collection method. The data analysis technique used in this study was content analysis. The study involved two subject participants, both of them are patient’s wife who become caregivers of their husband and two others significant person. The results showed that the subjects I stress conditions caused more by the attitude of husband who is fussy and dual role that must be endured since her husband suffered a stroke. Subjects I more independent economically and have adequate social support so that is more likely to use the problem-focused coping in the form of informational seeking and confronting coping. The subject I only uses emotion-focused coping when distressed and feels unable to change the conditions. As a housewife, subject II economically depends on her husband as the family backbone, therefore she feels that the heaviest stress condition perceived from economic problem besides taking care of her unruly husband. Subject II which does not have social support out of her family tends to use emotion-focused coping in the form of avoidance and seeking social support to endure in a situation which perceived depressing. It is found in this study that the using of religious coping helps acceptance of the conditions that must be endured by both subjects.Based on the results of the study, it can be concluded that the coping strategies used by each subject is influenced by social support and economic conditions underlying the subjects.